The Gruffalo's Child - Donaldson, Julia; Scheffler, Axel (New York : Puffin Books, 2007)
The Gruffalo's Child goes out to find the Big Bad Mouse she has heard so much about.
Originally published in Great Britain in 2004 by Macmillan Children's Books.
Keywords: Animals -- Fiction; Curiosity -- Fiction; Mice -- Fiction; Stories in rhyme